Efficacy of the adjuvanted recombinant zoster vaccine (RZV) by sex, geographic region, and geographic ancestry/ethnicity: A post-hoc analysis of the ZOE-50 and ZOE-70 randomized trials. Issue 43 (8th October 2019) - Willer, David O.; Oostvogels, Lidia; Cunningham, Anthony L.; Gervais, Pierre; Gorfinkel, Iris; Hyung Kim, Joon; Talarico, Carla; Wascotte, Valentine; Zahaf, Toufik; Colindres, Romulo; Schuind, Anne; ,
Highlights: RZV efficacy against HZ or PHN was similar in women and men. In ≥50-year-olds, efficacy against HZ was 95.7–97.2% across geographic regions. In ≥70-year-olds, efficacy against HZ and PHN was 86.8–100% across geographic regions. No major efficacy differences observed against HZ and PHN by geographic ancestry/ethnicity. RZV efficacy against HZ and PHN in these subsets was consistent with the overall ZOE-50/70 population. Abstract: Background: Herpes zoster (HZ) risk appears to vary by sex and geographic ancestry/ethnicity. Methods: In 2 randomized clinical trials, participants received 2 doses of adjuvanted recombinant zoster vaccine (RZV) or placebo intramuscularly, 2 months apart. In this post-hoc analysis, we investigate efficacy of RZV against HZ and postherpetic neuralgia (PHN) by sex, geographic region, and geographic ancestry/ethnicity in ≥50-year-olds (ZOE-50: NCT01165177) and ≥70-year-olds (pooled data from ZOE-50 and ZOE-70: NCT01165229). Results: Vaccine efficacy against HZ or PHN was similar in women and men. Across geographic regions, efficacy against HZ ranged between 95.7 and 97.2% in ≥50-year-olds, and between 87.3% and 95.1% in ≥70-year-olds; efficacy against PHN ranged between 86.8 and 100% in ≥70-year-olds. Across ancestral/ethnic groups, efficacy ranged between 88.1 and 100% against HZ and between 65.9 and 100% against PHN in ≥70-year-olds. Conclusions: While the ZOE-50/70 studies were not powered or pre-designed for these post-hoc analyses, RZV appears efficacious against HZ and PHN irrespective of sex, region, or geographic ancestry/ethnicity.